Indigenous youth justice programs evaluation - Bodean Hedwards
In this report, four programs that were already being implemented by states and territories and identified by them under the National Indigenous Law & Justice Framework as promising practice in diversion are examined. Executive summary Diversion from the youth justice system is a critical goal for addressing the overrepresentation of Indigenous young people in the criminal justice system. In this report, four programs that were already being implemented by states and territories and identified by them under the National Indigenous Law & Justice Framework as promising practice in diversion are examined. The programs were evaluated, as part of a broader initiative, to determine whether and on what basis they represent good practice (ie are supported by evidence). State and territory governments nominated the programs for evaluation. The four programs sit at different points along a continuum, ranging from prevention (addressing known risk factors for offending behaviour, such as disengagement from family, school, community or culture), early intervention (with identified at-risk young people), diversion (diverting from court process—usually for first or second time offenders) and tertiary intervention (treatment to prevent recidivism): • Aboriginal Power Cup (South Australia)—a sports-based program for engaging Indigenous young people in education and providing positive role models (prevention). • Tiwi Islands Youth Development and Diversion Unit (Northern Territory)—a diversion program that engages Tiwi youth who are at risk of entering the criminal justice system in prevention activities, such as a youth justice conference, school, cultural activities, sport and recreation (early intervention and diversion). • Woorabinda Early Intervention Panel Coordination Service (Queensland)—a program to assess needs and make referrals for young Indigenous people and their families who are at risk or have offended and have complex needs (early intervention and diversion). • Aggression Replacement Training (Queensland)—a 10 week group cognitivebehavioural program to control anger and develop pro-social skills, delivered to Indigenous and non-Indigenous youth assessed as ‘at risk’ of offending or reoffending (early intervention and tertiary intervention with offenders to reduce risk of reoffending). For each program, the evaluation team developed a ‘program logic’, identifying the activities and goals of the program, and how it articulates within a broader framework of criminal justice prevention. This informed the design of the evaluation and the approach to collecting both qualitative data (from young people participating in the program, program staff, family, or other service providers/community members) and quantitative data to identify any effects of the program on individuals, or the broader community